2022
DOI: 10.3389/fimmu.2022.951143
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cells targeting the ganglioside NGcGM3 control ovarian tumors in the absence of toxicity against healthy tissues

Abstract: Chimeric antigen receptor (CAR) T cells have emerged as a powerful immunotherapeutic tool against certain hematological malignancies but a significant proportion of patients either do not respond or they relapse, sometimes as a result of target antigen loss. Moreover, limited clinical benefit has been reported for CAR therapy against epithelial derived solid tumors. A major reason for this is the paucity of solid tumor antigens identified to date that are broadly, homogeneously and stably expressed but not fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…While that paper utilized CARs based on mouse/human VH/VL 14F7 derived scFv chimeras sourced from the same publication as the murine VH/VL scFv (14F7c1) used in the present study, all scFv variants showed comparable binding affinities (10). Although indications of in vitro CAR T cellmediated cytotoxicity against wild type SKOV3 cells was reported by Cribioli et al, the target-specific nature of these responses were not confirmed due to a lack of non-targeted CAR T cell controls (28). Similar to our results, no delay in tumor outgrowth was seen for wild-type human cancer cell xenografts, although the magnitude of GM3(Neu5Gc) acquisition during in vivo growth was not specifically addressed (28).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…While that paper utilized CARs based on mouse/human VH/VL 14F7 derived scFv chimeras sourced from the same publication as the murine VH/VL scFv (14F7c1) used in the present study, all scFv variants showed comparable binding affinities (10). Although indications of in vitro CAR T cellmediated cytotoxicity against wild type SKOV3 cells was reported by Cribioli et al, the target-specific nature of these responses were not confirmed due to a lack of non-targeted CAR T cell controls (28). Similar to our results, no delay in tumor outgrowth was seen for wild-type human cancer cell xenografts, although the magnitude of GM3(Neu5Gc) acquisition during in vivo growth was not specifically addressed (28).…”
Section: Discussionmentioning
confidence: 68%
“…A recent study by Cribioli et al demonstrated that peritumoral injection of 14F7 CAR T cells delays the outgrowth of CMAHexpressing SKOV3 ovarian cancer xenografts injected four days earlier (28). While that paper utilized CARs based on mouse/human VH/VL 14F7 derived scFv chimeras sourced from the same publication as the murine VH/VL scFv (14F7c1) used in the present study, all scFv variants showed comparable binding affinities (10).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…[225][226][227] Like for TCRs, most antigens targeted by CARs are TAA rather than TSA. We recently built CAR T cells against N-glycoslylated ganglioside monosialic 3 (NGcGM3) 228 with previously described scFv derived from the 14F7 monoclonal antibody (mAb) developed at the Center of Molecular Immunology (Havana, Cuba). 229,230 NGcGM3 is present on the surface of a range of cancers including ovarian, breast, melanoma, and lymphoma as a result of metabolic incorporation from dietary sources and it is associated with tumor growth and immune suppression.…”
Section: Ar T-cell Ther Apymentioning
confidence: 99%